Translocation, t(4q−;13q+), in three generations resulting in partial trisomy of the long arm of chromosome 4 in the fourth generation - Schrott, Helmut G. (1974)
The karyotype of a child with severe mental retardation, microcephaly, minor facial anomalies, and urinary tract outflow obstruction was found to be 46,XY,13q+mat. Trypsin-Giemsa banding studies showed an inherited translocation, t(4q−;13q+), in several asymptomatic members of the family including the propositus' mother. This indicates that the propositus had partial trisomy for the distal one-third of the long arm of chromosome 4. Review of the literature suggests that urinary tract and genital anomalies may be a consistent feature of this partial trisomy.